Bulk Loading of Emulsion Explosives in Shaft Sinking - R J. Roach; D Roy (International Society of Explosives Engineers, 1997)
After months of discussion on ways and means to improve productivity in the shaft sinking process, it was decided to look at those areas where, historically, methods have been stagnant for many years. These categories included drilling, hole diameter, drill patterns, explosive types, explosive loads, initiation techniques, cut design, wall control, fragmentation and heated magazines.